Budaya Pascamodernitas: Pergeseran Budaya Masyarakat Pedesaan di Selatan Pulau Bangka - Adnan, Adnan (SOSIOLOGI, 2009)
Generally rural society is farmers, although they are not a farmer basically, but they are always doing agricultural activity. This phenomenon especially represents individuality of rural society around the world. Now, this phenomenon slowly start to change with entry of information technology in their life socialize. Those way also knock over Bangka Islandâs society, especially the south region of this island. Economic crisis in Indonesia at 1998, but in this region is prosperity. Because of price of peppercorn at the global market make economics socialize here good progressively. A few times later, price of peppercorn breakdown, but price of tin start to go up, governance Regency of highest Bangkaâs governmental freeing society to mine tin (TI). This condition return to improve condition of economics socializes in this island is instantly. The recovery of economics of rural society is instantly, making rural societyâs culture get of friction instantly too. The real friction in pattern life of rural society, where rural society turn into consumptive society as one of postmodern culture signs.Â Postmodern culture in identical with global culture or the cultural globalization represent phenomenon where about has been happened by the abysmal process of modernity or abysmal of structuralism. This case marked: first, cultural influence and mass media becoming strong, in such a way social in life than previous era. Second, social and economic life more centered on consumption of symbol and life style than production of goods becoming individuality in industrial era. Third, attack or criticize for idea about reality and the representations. Fourth, the unifier from cultural production principle is image and space; there is no more narrations and history. Fifth, multifarious kinds of parody is grow up, pastiche, irony, kitsch, and pop eclectics. Sixth, forms architecture Urban show entertainment amusement extrusion symptom, " leha-leha", and the clearest life style see in shopping center (mall), amusement center, and the dwelling complex are like real estate, condominium, and the apartment. And seventh, Hybridity worshiped, rigidity distinctions (classifications, boundary, like boundary of among high culture or popular or low elite culture) progressively turn tail or is even left.